The Effectiveness of Drying on Residual Droplets, Microorganisms, and Biofilms in Gastrointestinal Endoscope Reprocessing: A Systematic Review - Hefeng Tian; Jiao Sun; Shaoning Guo; Xuanrui Zhu; Han Feng; Yijin Zhuang; Xiu Wang (Gastroenterology Research and Practice)
Background. Despite endoscope reprocessing, residual droplets remain in gastrointestinal endoscope working channels. Inadequate drying of gastrointestinal endoscope working channels may promote microbial reproduction and biofilm formation, increasing the risk of infection in patients. This review was designed to provide the current status of gastrointestinal endoscope drying, emphasize the importance of gastrointestinal endoscope drying, and evaluate the effectiveness of different drying methods of gastrointestinal endoscope in reducing residual droplets and microbial growth risk. Methods. A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting checklist. The PubMed, Web of Science, Medline, EMBASE, EBSCO, CNKI, CQVIP, and Wanfang Data databases were searched from 2010 to 2020 to identify eligible articles focused on methods of gastrointestinal endoscope drying and the status of endoscope drying. The following key points were analyzed: type of intervention, amount of residual droplets, major microbial types, and effectiveness of biofilm intervention. JBI quality assessment tool was used to determine bias risk for inclusion in the article. Results. This review included twelve articles. Two of the articles reported lack of drying of gastrointestinal endoscopes while the other ten reported residual droplets, microbial growth, and biofilm formation after different methods of drying. Four articles reported 0 to 4.55 residual droplets; four articles reported that the main microbial types were cocci and bacilli, most commonly Staphylococcus, Escherichia coli, Bacillus maltophilia, and Pseudomonas aeruginosa; and two reported that drying could effectively reduce biofilm regeneration. The type of intervention is as follows: automatic endoscopy reprocessor (AER), manual compressed air drying, and the Dri-Scope Aid for automatic drying and drying cabinet. Conclusions. While endoscope reprocessing may not always be effective, an automatic endoscope reprocessor plus the Dri-Scope Aid with automatic drying over 10 min or storage in a drying cabinet for 72 h may be preferred.